Who Owns Federal Reserve Losses and How Will They Impact Monetary Policy? - Paul H. Kupiec; Alex J. Pollock (American Enterprise Institute (AEI), 2022)
For the first time in its 108-year history, the Federal Reserve System faces massive and growing mark-to-market losses and is projected to post large operating losses in the near future. In a 2011 policy statement, the Federal Reserve Board outlined its plan to monetize system operating losses notwithstanding the (apparently) little-known fact that the Federal Reserve Act requires Federal Reserve member banks (the stockholders who own the Federal Reserve district banks) to share at least a portion of district reserve bank operating losses. Contrary to opinions expressed by Federal Reserve system officials, should the Fed abide by the legal requirements in the current version of the Federal Reserve Act, operating losses could impact monetary policy. If the Fed chooses to ignore the law and monetize operating losses, member banks will be in the enviable (if difficult to justify) position of directly benefiting from the current inflation. Because they are now paid interest on their reserve balances and receive guaranteed dividends on their Federal Reserve stock, member banks will monetarily benefit from the Fed's policy to fight inflation while the public bears Federal Reserve system losses. Meanwhile, the public at large will also face the costs of higher interest rates, reduced growth and employment and losses in their investment and retirement account balances. Should the public recognize the implications of the Fed's plan to monetize its operating losses, the Fed could face an embarrassing "communication problem".
Keywords: 330